Simulation-gaming : on the improvement of competence in dealing with complexity, uncertainty, and value conflicts : proceedings of the International Simulation and Gaming Association's 19th International Conference, Department of Gamma-Informatics, Utrecht University, the Netherlands, 16-19 August 1988 - Klabbers, Jan H. G. (Pergamon Press, 1989)
This volume records the Proceedings of the International Simulation and Gaming Association's 19th International Conference which took place at Utrecht University in 1988. Seven sections are contained in the volume. The first section on complexity, uncertainty and conflict deals with theoretical and methodological issues. This is the introduction to the conference theme "On the improvement of competence". The following sections cover broad areas: organizational change, business simulation, policy exercise, methodology, learning environments, and special topics such as environmental planning, health care, diplomatic games and gambling.